2019
DOI: 10.1002/hpm.2866
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effects of general practitioner–supported patient noncommunicable diseases control model in Shanghai, China

Abstract: Summary Noncommunicable diseases (NCDs) are the leading cause of death worldwide. A litmus test for China's health reform is its ability to effectively deal with NCDs. The general practitioners (GPs)–supported NCD control model was designed to address ways to effectively prevent and control NCDs population‐wide. This study aimed to evaluate the GPs‐supported NCD control model and its effect on China's NCD control. The model was structured with three layers of two‐way relationships between patients, GPs, and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Some provinces in the eastern region explored hypertension management at the primary care level. Beijing and Shanghai carried out community intervention trials for hypertension management before 2000 [ 50 ] and subsequently evaluated the effectiveness of the project [ 52 , 54 ]. The Disease Control Bureau of the former Ministry of Health selected 23 provinces for pilot projects in 2005 to explore the model and experience of standardized management of hypertension in the community, covering most provinces in the eastern region [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some provinces in the eastern region explored hypertension management at the primary care level. Beijing and Shanghai carried out community intervention trials for hypertension management before 2000 [ 50 ] and subsequently evaluated the effectiveness of the project [ 52 , 54 ]. The Disease Control Bureau of the former Ministry of Health selected 23 provinces for pilot projects in 2005 to explore the model and experience of standardized management of hypertension in the community, covering most provinces in the eastern region [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirmed the value of patient involvement through an empirical research, which implied health managers that patient active involvement in the doctor-patient consultation is helpful to coordinate patients' reasonable and efficient use of primary care. Establishing patient-centred health management strategies and making patients fully participate in primary health care, including the formulation of health plans and management of chronic disease, 76 will be conducive for patients' first choices and subsequent utilization of health services from primary health care facilities. Therefore, health managers should encourage patients to participate in the medical visits as much as possible by promoting and popularizing the shared medical decision as well as training physicians in developing skills to facilitate patient involvement and decision making.…”
Section: | Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends that countries take effective measures to prevent and treat diabetes [11]. Accordingly, the WHO and the National Institutes of Health reported that acupuncture could be an effective means to treat diabetes [12].…”
Section: Strengthening Acupuncture In Chinamentioning
confidence: 99%